Parents, friends, and classmates : reference groups and dropout from vocational education and training in Germany - Siembab, Matthias [Verfasser] (My University, 2024)
„This study examines the influence of social contexts on the decision to either complete or leave the first vocational education and training (VET) position among young German apprentices—an aspect that has received little attention in dropout research. In particular, the role of three reference groups—parents, friends and classmates at vocational school—in shaping this decision is examined. Using longitudinal data from the German National Educational Panel Study, the analysis addresses two key research questions: (1) Which reference groups are associated with the dropout decision? (2) And how do they influence the decision-making process? For this purpose, the study primarily investigates apprentices’ perceptions of the normative expectations and career ambitions of these groups, and compares the occupational achievements of apprentices and their parents. Two main results are found: (a) Parents and friends have a normative function; apprentices are more likely to complete their VET successfully if they believe that their parents and friends expect them to do so. (b) Both classmates and parents serve a comparative function; if apprentices perceive high career ambitions among their classmates, this may be intimidating and increase the risk of dropping out—in favor of switching to another training occupation. In addition, having parents with a higher occupational status seems to encourage apprentices to pursue a more demanding career path in the case of a change in training occupation. This study supports the notion that a multitude of actors contribute to the success of VET. Therefore, it could be beneficial for career guidance and counseling efforts to extend beyond individual counseling and consider actors who, although indirectly involved in VET, act as important reference groups for apprentices.“ (author’s abstract; BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; P 2.3 Auszubildende; G 1.3.2.2.2 Verlauf (Erfolg / Abbruch); 370; Berufsausbildung; Auszubildender; Ausbildungsabbruch; Ausbildungsabbrecher; Einflussfaktor; Eltern; Peer group; Bildungsaspirationen; Nationales Bildungspanel